2009
DOI: 10.1007/s00249-009-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of kinetics of thermal aggregation of mitochondrial aspartate aminotransferase by dynamic light scattering: protective effect of α-crystallin

Abstract: Thermal aggregation of aspartate aminotransferase from pig heart mitochondria (mAAT) has been studied at various temperatures and various protein concentrations by dynamic light scattering. The character of the dependence of protein aggregate size on time indicates that aggregation of mAAT proceeds in the regime of diffusion-limited cluster-cluster aggregation. Suppression of mAAT aggregation by alpha-crystallin is due to transition of the aggregation process into the regime of reaction-limited cluster-cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…[38][39][40] In fact, the addition of Arg resulted in the formation of denser aggregates than those in the absence of solution additives (see Figure 4). It is worth mentioning that a-crystallin 33,35,37 and GroEL 53 change the regime of protein aggregation from DLCA to RLCA. Both a-crystallin 56,57 and GroEL 58,59 prevent protein aggregation by stabilization of denatured protein via complexation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[38][39][40] In fact, the addition of Arg resulted in the formation of denser aggregates than those in the absence of solution additives (see Figure 4). It is worth mentioning that a-crystallin 33,35,37 and GroEL 53 change the regime of protein aggregation from DLCA to RLCA. Both a-crystallin 56,57 and GroEL 58,59 prevent protein aggregation by stabilization of denatured protein via complexation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated that start aggregates of protein appeared and the formation of the start aggregates proceeded as all-ornone principle without accumulation of intermediates, consistent with previous reports. [33][34][35][36][37] The mean value of the aggregate sizes changed toward the higher R h value with increasing incubation time. At t 5 16 min, no monomeric ly- sozyme was detected.…”
Section: Transmission Electron Microscopymentioning
confidence: 93%
See 2 more Smart Citations
“…The hydrodynamic radius of the start aggregates was tens of nanometers. The start aggregate formation was revealed in the process of thermal aggregation of the following model substrates: β L -crystallin from bovine lens [1], glyceraldehyde-3-phosphate dehydrogenase and glycogen phosphorylase b from rabbit skeletal muscle [2][3][4][5][6], aspartate aminotransferase from pig heart mitochondria [7] and tobacco mosaic virus coat protein [8].…”
Section: Introductionmentioning
confidence: 99%